The effects of plyometric warm-up on sprint performance in field hockey athletes / Aqmar Farhana Najwa Ahmad Fuad ... [et al.]. - Ahmad Fuad, Aqmar Farhana Najwa; Mohamed, Muhamad Noor; Md Radzi, Noor Azila Azreen; Saiful Annur, Muhamad Safiq; Mazaulan, Mardiana; Adnan, Mohd Aizzat; Abu Kassim, Nurul Ain; Shari, Maisarah; Raja Hussain, Raja Nurul Jannat (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Plyometric warm-ups are generally thought to be effective for enhancing sprint performance [1], yet their application in sport-specific contexts like field hockey remains underexplored. This study investigates the impact of different box height jumps on sprint performance over time, addressing critical gaps in sport-specific plyometric strategies to aid coaches in optimizing athlete sprinting ability [2]. Plyometric warm-ups are generally thought to be effective for enhancing sprint performance [1], yet their application in sport-specific contexts like field hockey remains underexplored. This study investigates the impact of different box height jumps on sprint performance over time, addressing critical gaps in sport-specific plyometric strategies to aid coaches in optimizing athlete sprinting ability [2].